The Relationship Between Work-Life Balance And Employee Retention In Public Organizations In Kuching, Sarawak - Angelina Melanie, Fabian (Universiti Malaysia Sarawak (UNIMAS), 2020)
Retaining employees has always been known as a challenge for most organization nowadays, apart from coping with globalisation issues. There are several strategies that can be practiced by organizations to ensure employee retention. Hence, the main purpose of this study is to determine the relationship between work-life balance and employee retention in public organizations in Kuching, Sarawak. The variables of work-life balance that are examined in this study includes flexible work schedule, job sharing and job exhaustion. This quantitative study used a total number of 92 employees of public organizations in Kuching, Sarawak as sample and data were collected by using questionnaires. The data were analysed by using Pearson’s Correlation Analysis to measure the relationship between variables. The finding shows that the variables that have significant relationship with employee retention are flexible work schedule and job sharing, while job exhaustion shows no significant relationship with employee retention.